Geographic and age variations in mutational processes in colorectal cancer - Díaz-Gay, Marcos; Dos Santos, Wellington; Moody, Sarah; Kazachkova, Mariya; Abbasi, Ammal; Steele, Christopher D; Vangara, Raviteja; Senkin, Sergey; Wang, Jingwei; Fitzgerald, Stephen; Bergstrom, Erik N; Khandekar, Azhar; et al. (Nature, 2025)
Incidence rates of colorectal cancer vary geographically and have changed over time1. Notably, in the past two decades, the incidence of early-onset colorectal cancer, which affects individuals below 50 years of age, has doubled in many countries2-5. The reasons for this increase are unknown. Here we investigate whether mutational processes contribute to geographic and age-related differences by examining 981 colorectal cancer genomes from 11 countries. No major differences were found in microsatellite-unstable cancers, but variations in mutation burden and signatures were observed in the 802 microsatellite-stable cases. Multiple signatures, most with unknown aetiologies, exhibited varying prevalence in Argentina, Brazil, Colombia, Russia and Thailand, indicating geographically diverse levels of mutagenic exposure. Signatures SBS88 and ID18, caused by the bacteria-produced mutagen colibactin6,7, had higher mutation loads in countries with higher colorectal cancer incidence rates. SBS88 and ID18 were also enriched in early-onset colorectal cancers, being 3.3 times more common in individuals who were diagnosed before 40 years of age than in those over 70 years of age, and were imprinted early during colorectal cancer development. Colibactin exposure was further linked to APC driver mutations, with ID18 being responsible for about 25% of APC driver indels in colibactin-positive cases. This study reveals geographic and age-related variations in colorectal cancer mutational processes, and suggests that mutagenic exposure to colibactin-producing bacteria in early life may contribute to the increasing incidence of early-onset colorectal cancer.
Keywords: Russia; Male; kolorektální nádory; mutace; Brazil; Microsatellite Instability; Colombia; Argentina; Age of Onset; Thailand; věk při počátku nemoci; mikrosatelitní nestabilita; mutace INDEL; Polyketides; Adult; mutační rychlost; Age Factors; Aged; dospělí; Thajsko; mužské pohlaví; senioři; Mutation Rate; incidence; Mutagens; Brazílie; polyketidy; mutageny; lidé; ženské pohlaví; Humans; Kolumbie; věkové faktory; Rusko; Peptides; peptidy; Colorectal Neoplasms; Mutation; INDEL Mutation; Female; lidé středního věku; Incidence; Middle Aged